KONDISI TERUMBU KARANG DI GUGUSAN KARANG UTAMA BLOK MIGAS TOILI, SULAWESI TENGAH - Tis'in, Musayyadah; Mansyur, Kasim (AgriSains, 2016)
MIGAS Block of Toili, Tolo Bay, Central Sulawesi Province has been developed by Joint Operating Body Pertamina Medco E&P Tomori South since 2004. There are 8 main coral sandbas located this block. Those are Taka Tiaka, Tambaga, Mbunginang, Takasuda, Ranggasang, Lana’ang, Buntar and Pakangkah Alonya. Corals reefs as primary component in marine ecosystem have important roles for the sustainability of fisheries resources that utilized by local fishermen. Also, corals have been used as indicators for assessing the health of the ecosystem, primarily for assessing the impact of the activity reated to fishery and oil and gas exploitation in Toili Block. This research used line interception transect to measure the growth  and long life form of coral. The Analysis was based on percentage of coral cover (English et al., 1997). The Corals Mortalitas Indeks is use to asses canges life hard corals to be dead corals. Mortality index was used to asses the change from live to dead coral. The determination of coral reefs condition was referred to Ministrial Decree No: KEP-04/MENLH/02/2001. Coral cover percentage found in Tiaka was 28,82%-68,70% (IM 0,59 and 0,13); Taka Tambaga 9,70%-55,66% (IM 0.89-0,38); Taka Suda’ 13,44%-42,62% (IM 0.72-0,52); Taka Mbunginang 21,68%-48,36% (IM 0.76-0,43); Taka Ranggassang 20,64%-42,00% (IM 0.70-0,50); Taka Lana’ang  26,92%-53,5% (IM 0.73-0,37); Taka Buntar 24,08%-38,94% (IM 0.70-0,51) and Taka Pakangkah Alonerya 77,24%-72,16% (IM 0.08-0,17). Coral reefs that found along the coastal water of Central Sulawesi particularly by the terrestrial area mostly in bad to moderate condition while those that opposed to the open sea ((Tolo Bay) are found to have moderate to very good condition.Keywords: coral reefs, condition, block toili.